2021
DOI: 10.1142/s0192415x21500518
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Decoctions Significantly Reduce the Mortality in Severe and Critically Ill Patients with COVID-19: A Retrospective Cohort Study

Abstract: Coronavirus disease (COVID-19) is a new infectious disease associated with high mortality, and traditional Chinese medicine decoctions (TCMDs) have been widely used for the treatment of patients with COVID-19 in China; however, the impact of these decoctions on severe and critical COVID-19-related mortality has not been evaluated. Therefore, we aimed to address this gap. In this retrospective cohort study, we included inpatients diagnosed with severe/critical COVID-19 at the Tongren Hospital of Wuhan Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…A high-quality RCT [ 26 ] we included indicated that the mortality rate of severe or critical patients in TCM group was visibly lower compared with CWM group [38.6% (22/57) vs 75.9% (41/54), RR = 0.51, 95% CI (0.35, 0.73), P = 0.0002]. Five RSs [ 52 , 54 , 55 , 57 , 58 ] reached the same conclusion [RR = 0.47, 95% CI (0.31, 0.70), I 2 = 54%, P = 0.0002] (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…A high-quality RCT [ 26 ] we included indicated that the mortality rate of severe or critical patients in TCM group was visibly lower compared with CWM group [38.6% (22/57) vs 75.9% (41/54), RR = 0.51, 95% CI (0.35, 0.73), P = 0.0002]. Five RSs [ 52 , 54 , 55 , 57 , 58 ] reached the same conclusion [RR = 0.47, 95% CI (0.31, 0.70), I 2 = 54%, P = 0.0002] (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study was a survey that included patient data from two regions, Hong Kong and mainland China, separately, so we analyzed the data separately ( 71 ). Twenty-two studies were conducted in China ( 27 , 31 – 34 , 37 , 39 , 40 , 44 , 47 , 55 , 62 – 65 , 67 , 69 – 73 , 75 – 77 ), six in Saudi Arabia ( 18 , 21 – 23 , 25 , 26 ), five in India ( 10 , 41 , 46 , 60 , 61 ), three in the United States ( 35 , 42 , 45 ) and three in Turkey ( 38 , 49 , 66 ), and these were the most frequent countries included in this review. Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 – 31 , 35 , 42 , 43 , 45 , 48 – 54 , 57 – 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 – 31 , 35 , 42 , 43 , 45 , 48 – 54 , 57 – 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 – 34 , 37 , 39 , 40 , 44 , 47 , 55 , 63 – 65 , 67 , 69 – 73 , 75 – 77 ), functional food (supplements) or herbs ( n = 20) ( 17 – 24 , 29 , 36 , 38 , 43 , 49 – 52 , 57 – 59 ), mind-body practice or spiritual practice ( n = 9) ( 28 , 35 , 42 , 45 , 48 , 54 , 60 , 61 , 74 ), Ayurveda ( n = 2) ( 10 , 41 ), homeopathy ( n = 1) ( ...…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the focus and difficulties in the treatment of COVID-19 concern mainly the more severe and critical cases, which are also the main factors directly affecting mortality [27] . There is no definite and effective treatment for the more severe and critical COVID-19 patients in modern medicine, but the intervention of TCM or integrated traditional Chinese and Western medicine according to the clinical symptoms of the more severe and critical COVID-19 patients can help to reduce mortality and improve prognosis [22] , [25] , [27] , [228] . The gut microbiota in severe and critical COVID-19 patients is disordered, rendering it prone to bacterial infection and further aggravating the disease.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%